Kajian Perancangan dan Evaluasi PLTMH Jorong Patamuan Kabupaten Pasaman dalam Mengatasi Kekurangan Listrik Pedesaan - N Nusyirwan (METAL: Jurnal Sistem Mekanik dan Termal, 2017)
Electrical energy supply which is not evenly distributed throughout the territory of Indonesia is mainly due to the width of the area the limitation on the budget. This condition has enforcing the rural residents to make their own electric energy generation. The discovery of a compact electric generator with control equipment that is reliable in a variety of sizes and power capacities has increasing the development of small size hydro electric power plants. One of the technology challenges for this power plant is to design a power plant with the existing water resources and equipment available on the market. Base on the preliminaries study in MHP Jorong Patamuan, it is found that the cross-flow turbines with a maximum power of 10 Kw is more appropriate for the electrical generator. The Maximum head for this micro hydro generator is 8 meters and the net loss of 0.4 m. The main channel is composed of a trunk made of concrete channels open with a size of 40 x 40 x 40 cm and a pipeline for rapid pipeline with a length of 28 m using the pipe 8 inches or 20 cm. Generator been Generator one Phase with 10 Kw power. There are constraints in this PLMH operation, which is the state annual river discharge decreased during July and August due to the long dry season so that the water flow is only 0.08 m3 / s, far below the planned discharge 0.2252 m3 / s for the power wat 3000 output only approximately 1/3 of the nominal power 10000 watt than planned.